Words in progress contro l’odio. Pratiche artistiche ed espressivo-corporee dentro e fuori la scuola - Pomari, Laura; Riccardi, Vaninka; Villa, Roberta (Antropologia Pubblica, 2024)
We present a project of intervention in a conflictual situation at a kindergarten, due to a different educational model of the teachers and the migrant families. The methodology arises from the mix between theatre and anthropology practice: the team are composed of two theatrical operators, a cultural anthropologist and a psychomotricist; the professional experience involve artistic and expressive-body practices as social change agents. The project is structured through different action within and for the school and then open up to the territory; particularly I Racconti in Lingua Madre for the families and the training Sentire e Comprendere for teachers. The action against hate promotes change and development as a part of the educating community through the purpose to build a self-learning school. The result of the project is a bridge of relationships between school and families, working on the sense of belonging to a common social fabric.